2023
DOI: 10.31849/lectura.v14i1.12031
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Blended Learning terhadap Hasil Belajar Siswa Sekolah Dasar

Abstract: Kurikulum merdeka belajar Sekolah Dasar (SD) adalah upaya untuk mengubah sistem pendidikan menjadi lebih baik dan menempatkan SD pada jalur untuk mencapai tujuan dan sasaran yang tepat dan sesuai. Ketika satuan pendidikan dasar memiliki kurikulum merdeka, guru memiliki keleluasaan untuk merencanakan rencana kegiatan sekolah dan modul pengajaran untuk memfasilitasi pembelajaran sesuai dengan tingkat kemampuan siswa. Tujuan penelitian ini adalah untuk menemukan pengaruh model Blended Learning terhadap hasil bela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As in the research of manik & harahap (2021) reported that the implementation of discovery learning can improve student learning outcomes in learning Biology on the structure and function of animal tissues. (Irwandi & Putri, 2023) research shows that the implementation of blended learning has an influence on the learning outcomes of high school biology students. Research by (Rizqiah et al, 2023) which reported that the use of the Ruangguru application can improve the learning outcomes of Biology Class XI students.…”
Section: Cognitive Learning Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…As in the research of manik & harahap (2021) reported that the implementation of discovery learning can improve student learning outcomes in learning Biology on the structure and function of animal tissues. (Irwandi & Putri, 2023) research shows that the implementation of blended learning has an influence on the learning outcomes of high school biology students. Research by (Rizqiah et al, 2023) which reported that the use of the Ruangguru application can improve the learning outcomes of Biology Class XI students.…”
Section: Cognitive Learning Outcomesmentioning
confidence: 95%
“…Blended learning is learning that combines face-to-face learning with online learning (Ahmad et al, 2021). According to (Irwandi & Putri, 2023), the implementation of blended learning has an influence on high school students' Biology learning outcomes. One of the features in the Ruangguru application that is free and supports blended learning is the Ruangkelas feature.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of these curriculum changes aims to perfect the previous curriculum. In addition, curriculum changes are also tailored to the needs and development of the times (Puspita & Tirtoni, 2023). It could be classified into two categories: curriculum development before and after independence (Faisal & Martin in Setiawan & Suwandi, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Educational institutions provide curricula with the aim of improving the quality of teaching. Puspita & Tirtoni, (2023), the aim of the independent curriculum in elementary schools is to take the education system in a brighter direction and place elementary schools on a logical and correct path towards its goals and objectives. This curriculum helps prepare the country's future generations to face the challenges of the industrial revolution 4.0 by prioritizing freedom and independence (Alfath et al, 2022).…”
Section: Introductionmentioning
confidence: 99%